Regulation of estrogen receptor signaling in breast carcinogenesis and breast cancer therapy - Zhou, Zhuan (2013)
Estrogen and estrogen receptors (ERs) are critical regulators of breast epithelial cell proliferation, differentiation, and apoptosis. Compromised signaling vis-à-vis the estrogen receptor is believed to be a major contributing factor in the malignancy of breast cells. Targeting the ER signaling pathway has been a focal point in the development of breast cancer therapy. Although approximately 75 % of breast cancer patients are classified as luminal type (ER(+)), which predicts for response to endocrine-based therapy; however, innate or acquired resistance to endocrine-based drugs remains a serious challenge. The complexity of regulation for estrogen signaling coupled with the crosstalk of other oncogenic signaling pathways is a reason for endocrine therapy resistance. Alternative strategies that target novel molecular mechanisms are necessary to overcome this current and urgent gap in therapy. A thorough analysis of estrogen-signaling regulation is critical. In this review article, we will summarize current insights into the regulation of estrogen signaling as related to breast carcinogenesis and breast cancer therapy.